Azuichi, short utterance and responses in Japanese conversation on interview context - Shariff, Muhammad Haikal; Mamat, Roslina (2015)
Azuichi, short utterance, and responses are some of the Japanese linguistic features. They hold the significant meaning such as showing agreement, continuation of the conversation, politeness, and other functions from the listener to the speaker. This paper aimed to analyse the aizuchi, short utterance, and responses in the interview context by the Japanese native speaker. By using 15 episodes of Easy Japanese videos, the study found some of the types of azuichi, short utterance, and response produced by the interviewee in the interview conversation. The azuichi (hai), short utterance (hai), and response (hai) marked the most occurrence in the interviewee utterances. Each hai held the significant functions to maintain the naturalness of Japanese conversation. In conclusion, future studies need to done to involve the interviewer and interviewee's production of azuichi, short utterance, and response using similar approach.